2006
DOI: 10.1186/1743-422x-3-63
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Plaque assay under Avicel-containing overlay media is easier, faster and more sensitive than assays under agar- and methylcellulose overlays. The assay can be readily performed in a 96-well plate format and seems particularly suitable for high-throughput virus titrations, serological studies and experiments on viral drug sensitivity. It may also facilitate work with highly pathogenic agents performed under hampered conditions of bio-safety labs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
262
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 445 publications
(271 citation statements)
references
References 3 publications
3
262
0
Order By: Relevance
“…The HA molecules of influenza A viruses isolated from different hosts differ in their ability to recognize different cellular receptors in which the linkage between sialic acid and galactose of the carbohydrate chain is either ␣(2,3) or ␣ (2,6). HA molecules of human viruses preferentially bind to ␣(2,6)-linked receptors, those of avian and equine viruses bind to ␣(2,3)-linked, and those of swine viruses bind to both (1)(2)(3)(4)(5)(6)(7)(8)(9). Thus, ␣(2,3)-linked and ␣(2,6)-linked receptors are also referred to as avian and human receptors, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The HA molecules of influenza A viruses isolated from different hosts differ in their ability to recognize different cellular receptors in which the linkage between sialic acid and galactose of the carbohydrate chain is either ␣(2,3) or ␣ (2,6). HA molecules of human viruses preferentially bind to ␣(2,6)-linked receptors, those of avian and equine viruses bind to ␣(2,3)-linked, and those of swine viruses bind to both (1)(2)(3)(4)(5)(6)(7)(8)(9). Thus, ␣(2,3)-linked and ␣(2,6)-linked receptors are also referred to as avian and human receptors, respectively.…”
mentioning
confidence: 99%
“…We now have a detailed understanding of the molecular determinants for the different receptor specificity of different subtypes of influenza A virus HAs, in particular for H1, H2, and H3 subtypes that infect humans (1)(2)(3)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). For H2 and H3 HAs, it is predominantly determined by residues at 226 and 228 (Leu-226 and Ser-228 in human HAs and Gln-226 and Gly-228 in avian HAs, following the numbering convention for H3 HA) (5,7,11,21,(29)(30)(31). However, H1 HAs are different in this regard: although human and avian H1 HAs recognize ␣(2,6)-linked or ␣(2,3)-linked receptors, respectively, they both have Gln-226 and Gly-228.…”
mentioning
confidence: 99%
“…58) However, if the avian H5N1 virus acquires a mutation in receptor binding properties from avian type to human type (SA2-3Gal→SA2-6Gal) by the reverse mechanism of only two sets of amino acid exchange described above (Gln222→Leu; Gly 224→Ser, shown as a numbering of H5; Gln226→Leu; Gly228→Ser, shown as H3 subtype numbering), which allows human-to-human transmission, this highly pathogenic virus will spread quickly cause a pandemic. We have already observed that receptor binding specificity of hemagglutinin has changed during circulation in humans since its introduction from avian viruses.…”
mentioning
confidence: 99%
“…NA stalk deletions have been shown to reduce the enzymatic activity of the protein [14] and, presumably, adversely affect the spread of the virus to uninfected cells. Secondly, changes in the HA gene that compensate for a shortened N stalk have been described, including increased glycosylation near the receptor binding site thereby decreasing receptor binding affinity [15,16]. Sub-lineage I displayed this hyperglycosylation, with five predicted N-glycosylations sites in the HA gene compared to only three in sub-lineage II, which did not contain the Nstalk deletion.…”
Section: Fig 2 Unrooted Phylogenetic Tree Of the H6 Ha Nucleotide Sementioning
confidence: 99%